Use of Silica Supported Acid Catalyst in Organic Synthesis - Revika , Arora (Challenges and Advances in Chemical Science Vol. 9, 2022)
The use of solid supported reagents is increasing, due to their tremendous potential to offer green chemical technologies. Now-a-days, silica supported acid catalysts have gained much importance due to their high activity. Moreover, silica-supported reagents are easy to handle, less toxic, can be easily separated and reused, due to which they may play important role both in academia and industries. Silicas generally require no pre-swelling, which makes their use far simpler. As oxidative bromination of alkenes is very important in synthesizing biologically and synthetically important dibromocompounds, a simple, efficient and cost effective method has been used for the bromination of alkenes by using SiO2 -H2SO as solid heterogeneous catalyst. The objective of the study presented in this paper is to provide an environment friendly procedure for oxidative bromination of alkenes. Here, solid heterogeneous catalyst is used for synthesis of dibromo compounds.